Leptin in Sarcopenic Visceral Obesity: Possible Link between Adipocytes and Myocytes - Kohara, Katsuhiko; Ochi, Masayuki; Tabara, Yasuharu; Nagai, Tokihisa; Igase, Michiya; Miki, Tetsuro (PloS one, 2011)
The combination of sarcopenia, age-related loss of muscle strength and mass, and obesity has been recognized as a new category of obesity among the elderly. Given that leptin has been hypothesized to be involved in the pathogenesis of sarcopenic obesity, we investigated the relationship between plasma leptin levels and thigh muscle sarcopenia and visceral obesity. Thigh muscle cross-sectional area (CSA) and visceral fat area were measured using computed tomography as indices for muscle mass and visceral fat, respectively, in 782 middle-aged to elderly subjects (303 men and 479 women), participating in a medical check-up program. Visceral obesity was defined as visceral fat area >100 cm², and sarcopenia was defined as < (one standard deviation--mean of thigh muscle CSA/body weight of young subjects [aged <50 years]).Thigh muscle CSA was significantly and negatively associated with plasma levels of leptin in both men (β = -0.28, p<0.0001) and women (β = -0.20, p<0.0001), even after correcting for other confounding parameters, including age, body weight, body height, visceral fat area, blood pressure, homeostatic model assessment index, and high sensitive C reactive protein. Subjects were divided into four groups based on presence or absence of sarcopenia or visceral obesity. Plasma levels of leptin were higher in subjects with sarcopenic visceral obesity than in those with either sarcopenia or visceral obesity alone. These findings indicate that sarcopenic visceral obesity is a more advanced, and suggest that leptin may link visceral obesity and sarcopenia.